Proceedings of the 2005 International ACM SIGGROUP Conference on Supporting Group Work - GROUP '05 2005
DOI: 10.1145/1099203.1099216
|View full text |Cite
|
Sign up to set email alerts
|

A survey of collaborative information seeking practices of academic researchers

Abstract: Information seeking and management practices are an integral aspect of people's daily work. However, we still have little understanding of collaboration in the information seeking process. Through a survey of collaborative information seeking practices of academic researchers, we found that researchers reported that (1) the lack of expertise is the primary reason that they collaborate when seeking information; (2) traditional methods, including face-to-face, phone, and email are the preferred communication med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 11 publications
1
30
0
2
Order By: Relevance
“…With face-to-face meetings not always being practical or cost effective for virtual teams, the ability to share technical information or collaborate with fellow team members becomes even more important [30]. The quality of information within web conferencing relies on two major components: the quality of the information provided by the presenters and the quality of the technology delivering that information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With face-to-face meetings not always being practical or cost effective for virtual teams, the ability to share technical information or collaborate with fellow team members becomes even more important [30]. The quality of information within web conferencing relies on two major components: the quality of the information provided by the presenters and the quality of the technology delivering that information.…”
Section: Discussionmentioning
confidence: 99%
“…The sharing of information in organizations often needs to be made more effective [30]. When collaboration is performed through web-based communication systems, research has shown that it assists with deeper learning, shared understanding, critical thinking and better retention of information [16].…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Başka bir çalışmada ise, yukarıda belirtilen tetikleyicilerden parçalanmış bilgi kaynakları hariç diğerleri tetikleyici faktör olarak belirtilmiş ve evren olarak akademisyenleri ele alan çalışmada akademisyenler arasında her ne kadar bilginin karmaşıklığı ve erişilebilirliği tetikleyici olsa da, asıl tetikleyici unsurun alan uzmanlığı olduğu belirtilmiştir (Spence, Reddy ve Hall, 2005).…”
Section: Ortak Bilgi Davranışındaki öNemli Unsurlarunclassified
“…Accordingly, a great amount of research in the IR domain mostly dealt with both the design of enhanced document ranking models and a deep user's behavior understanding with the aim of improving an individual search effectiveness. However, in practice, collaboration among a community of users is increasingly acknowledged as an effective mean for gathering the complementary skills and/or knowledge of individual users in order to solve complex shared search tasks, such as fact-finding tasks (e.g., travel planning) or exploratory search tasks [13,18]. Collaboration allows the group achieving a result that is more effective than the simple aggregation of the individual results [14].…”
Section: Introduction and Tutorial Objectivesmentioning
confidence: 99%